2015
DOI: 10.1038/nclimate2816
|View full text |Cite
|
Sign up to set email alerts
|

Conservation policy and the measurement of forests

Abstract: Deforestation is a major driver of climate change 1 and the major driver of biodiversity loss 1,2 . Yet the essential baseline for monitoring forest cover-the global area of forests-remains uncertain despite rapid technological advances and international consensus on conserving target extents of ecosystems 3 . Previous satellite-based estimates 4,5 of global forest area range from 32.1 × 10 6 km 2 to 41.4 × 10 6 km 2 . Here, we show that the major reason underlying this discrepancy is ambiguity in the term 'fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
160
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 167 publications
(164 citation statements)
references
References 27 publications
3
160
0
1
Order By: Relevance
“…Changing definitions through time, they argued, explain the apparently alarming deforestation in several West African countries. The problem of defining forest is a general one in tropical landscapes [54][55][56]. Ratnam et al [57] provided a functional definition for distinguishing forest from 'savanna' based not on the trees but on the presence of a highly flammable, shade-intolerant C4 grassy understory in savannas and its absence in forests.…”
Section: The Antiquity Of Savannasmentioning
confidence: 99%
“…Changing definitions through time, they argued, explain the apparently alarming deforestation in several West African countries. The problem of defining forest is a general one in tropical landscapes [54][55][56]. Ratnam et al [57] provided a functional definition for distinguishing forest from 'savanna' based not on the trees but on the presence of a highly flammable, shade-intolerant C4 grassy understory in savannas and its absence in forests.…”
Section: The Antiquity Of Savannasmentioning
confidence: 99%
“…Sexton et al [25] found that the global forest maps with coarse resolutions showed a large discrepancy. However, the performance and consistency of the aforementioned eight medium resolution forest maps in China are still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…This is a difficulty even for humans visually interpreting tree cover from HRSI (<5 m resolution) data. However, this apparent confusion implies that the definition of what is a tree is of primary importance and spatially consistent [47]. The TTE, in particular, is a region in which this distinction is blurred.…”
Section: The Importance Of Height In Estimates Of Covermentioning
confidence: 99%
“…From discrete, small-footprint LiDAR returns, tree cover is calculated by dividing the number of returns above a criterion height by the total number of returns within a given sample [45,46]. In accordance with the International Geosphere-Biosphere definition of forests, Sexton et al specified the height criterion as 5 m, but this parameter may be tuned to biome-specific definitions of tree height [34,47].…”
Section: Assessing Spaceborne Maps Of Tree Cover Across the Ttementioning
confidence: 99%